Climate change: Impacts on outdoor activities in the summer and shoulder seasons. (June 2021) - Pröbstl-Haider, Ulrike; Hödl, Claudia; Ginner, Kathrin; Borgwardt, Florian
Abstract: The summer tourism market in Austria builds significantly on the country's opportunities for outdoor recreation such as mountaineering, mountain biking or water sports. This paper looks at the most important activities from a tourism perspective and considers the likelihood of impacts by climate change based on an extended literature review. It also examines current trends in tourism demand and concludes with both general and activity-specific adaptation and mitigation measures. The data collection and review process covered the relevant peer reviewed and grey literature. This comprehensive process was based on, and was open to, contributions by the full scientific community of relevant Austrian researchers and experts. The compilation process of the report followed quality standards such as the involvement of international partners as review editors within the review process. For many activities, climate change will lead to a prolongation of the season, which is an advantage for destinations focusing on hiking, biking, swimming, water sports, air sports and golf. However, it can be shown that climate-induced phenomena will have a strong impact on many of these activities, such as climbing and alpine touring, fishing, golf, and water and air sports. Here, the impacts may even lead to a change of destination or activity. Adaptation opportunities are rather limited in these cases. For other activities, adaptation measures can be applied to maintain the existing tourism offer. Irrigation can be increased in the case of golf courses, the construction of pools is feasible to compensate for deteriorated lakes, and destroyed trails and other hiking infrastructure, such as alpine hazard protection, could be reconstructed. However, all these measures are cost-intensive and may have a negative influence on the overall holiday experience. An early warning system via media (based on heat, thunderstorms and heavy rain) would be important to enable adaptation measures for companies and guests. Management implications: The discussion over different adaptation strategies is of great importance for tourism management. The paper presents four major strategies: ∙ Adaptation of the natural conditions: In this case, vulnerability can be reduced by improving the natural conditions, e.g. saving water by redesigning golf courses to improve fish habitats. ∙ Technical adaptation of the infrastructure: Technical solutions such as irrigation, artificial pools, artificial canoe routes or the reconstruction of trails maintain the important tourism functions. ∙ Technical adaptation of the equipment: the goal is an improvement of the equipment in order to continue the activity (e.g. type of boat, type of hang glider). ∙ Awareness raising, information and early warning systems : For many activities, an early warning system would be helpful to avoid risky situations due to flooding, rockfall, thunder storms or extreme heat.